European plurilingualism from a national language perspective - Nećak Lük, Albina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
The expected flow of information, people and goods within the United Europe requires a reflection regarding efficient communication among different language communities, across language and cultural boundaries. This aim shouldbe achieved by means of expanded offer and intensive learning of foreignlanguages in the EU member states. The ability of communication in several languages should make it possible for the population of member states and member candidates to enjoy equal starting-point conditions at the challenges of growing international mobility in the United Europe it should strengthen cooperation in the fields of education, culture and science, as well as in commerce and industry, and contribute to the overcoming of prejudice and elimination of discrimination. Multilingualism is in the processof becoming a sort of an identity card of European citizenship.The multilingualism of citizens - a good command of a national language being a main prerequisite here - should therefore contribute not only to better understanding and tolerance, but also to respect of language identity and cultural diversity of Europe. Despite this, a number of questions is being raised regarding the future status and functions of national languages in relation to the emerging European multilingualism. Especially lesser used languages, including Slovene, ought to have an elaborate, integral strategy and tactics. The article brings a few reflections on language issues in Slovenia in the European Year of Languages.
Keywords: Evropa; Europe; European Union; Evropska unija; multikulturnost; večjezičnost; jezikovna politika; jezikovne manjšine